Evaluating the Efficacy of a Cognitive Skills Training Program for Spanish-Speaking Adults with Subjective Cognitive Complaints. (30th August 2019) - Patino, Y; Sinclair, P; Osher, J; Torres, K
Abstract: Objective: The purpose of this pilot study was to examine the efficacy of a five-week Spanish cognitive skills training program on 18 participants with subjective cognitive complaints. Participants and Method: Eighteen Spanish-speaking participants completed a series of cognitive and emotional measures pre- and post-training, including objective measures of cognitive functioning (Montreal Cognitive Assessment, Spanish-version; MoCA), self-reported mood measures (Beck Depression Inventory, BDI; Beck Anxiety Inventory, BAI-Spanish version), and subjective cognitive complaints questionnaire (Subjective Cognitive Decline Questionnaire, Spanish version). Drawing from existing literature on effective interventions for subjective cognitive impairment (Reijnders et al., 2015), this research focused on delivering a five-week intervention program in Spanish, which included psychoeducation on cognition, cognitive strategy training, and applied practice of mindfulness techniques. Furthermore, this intervention incorporated Personalismo and indirect communication, which was applied by engaging with participants in a warm and culturally appropriate manner (Jiménez et al., 2014). Results: Participants demonstrated significant improvement in overall MoCA scores. Improvements in subjective cognitive performance, as well as decreases in depression and anxiety (as indicated by the BDI and BAI, respectively) were noted. Results also showed that changes in mood, anxiety, and subjective cognitive performance were not predictive of improvements in MoCA performance, lending support to the hypothesis that skills learned in the program contributed to improved cognitive performance. Conclusions: Overall, these results demonstrate that linguistically and culturally tailored psychoeducation regarding cognition, cognitive skills training, and mindfulness, can positively impact subjective and objective cognitive performance, as well as psychological wellbeing among Spanish-speaking adults. References: Jiménez, A.L., Alegría, M., Camino-Gaztambide, R.F., & Zayas I, L.V. (2014) Cultural sensitivity: What should we understand about Latinos? In R. Parekh (ed.)  The Massachusetts General Hospital Textbook on Diversity and Cultural Sensitivity in Mental Health  (pp.61-70). New York, NY: Springer. Rebok, G. W., Ball, K., Guey, L. T., Jones, R. N., Kim, H. Y., King, J. W., … ACTIVE Study Group (2014). Ten-year effects of the advanced cognitive training for independent and vital elderly cognitive training trial on cognition and everyday functioning in older adults.  Journal of the American Geriatrics Society,   62 (1), 16–24. doi:10.1111/jgs.12607.